Effects of Different Exercise Strategies and Intensities on Memory Performance and Neurogenesis - Diederich, Kai; Bastl, Anna; Wersching, Heike; Teuber, Anja; Strecker, Jan-Kolja; Schmidt, Antje; Minnerup, Jens; Schäbitz, Wolf-Rüdiger (Frontiers in Behavioral Neuroscience, 2017)
It is well established that physical exercise affects both hippocampal neurogenesis and memory functions. Until now, distinctive effects of controlled and voluntary training on behavior and neurogenesis as well as interactions between exercise intensity, neurogenesis and memory performance are still elusive. The present study tested the impact of moderate controlled and voluntary training on memory formation and hippocampal neurogenesis and evaluated interactions between exercise performance, learning efficiency and proliferation of progenitor cells in the hippocampus. Our data show that both controlled and voluntary training augmented spatial learning and promoted hippocampal neurogenesis. Regression analysis revealed a significant linear increase of the amount of new hippocampal neurons with increased exercise intensity. Regression analysis of exercise performance on retention memory performance revealed a quadratic, inverted u-shaped relationship between exercise performance and retention of spatial memory. No association was found between the amount of newborn neurons and memory performance. Our results demonstrate that controlled training, if performed with an appropriate combination of speed and duration, improves memory performance and neurogenesis. Voluntary exercise elevates neurogenesis dose dependently to high levels. Best cognitive improvement was achieved with moderate exercise performance.